Peningkatan Hasil Belajar IPA melalui Scientific Pro Simple Vehicle pada Materi Gerak Benda - Handayani, Rini Eka (Universitas Muhammadiyah Magelang, 2021)
The purpose of this research is to increase the learning result through the learning process with project based learning (PjBL), assisted by Simple Vehicleapproaches in scientific. The study employed class action study methods. The research model used is a cycle model developed by the kemmis and taggart. The study is carried out at the country junior high 1 Magelang, the town of Magelang on 2019/2020 lesson year. The study subject is a VIIIG class of students with a total of 30 children, whom there are 15 boys and 15 girls. The method of data collection are to use documentation, observation, tests, and interviews. The research is done in two cycles. The I cycle with the Simple Vehiclearrangement and the use of products on GLB and cycle II learning is made up of Simple Vehicleuse for Newton's third law and a data based GLB and GLBB charts. Through both cycles, the result of VIIIG class learner’s learning on motion materials through a scientific based project Simple Vehicleapproach at country junior 1 Magelang lesson 2019/2020 has been an increase from aged 78.0 to 82.9 in the first cycle, then the avarage 84.5 in the second cycle. That way, the Simple Vehiclecan be designated as one of the learning model for class VIII junior high school.